Efficacy of gefitinib at reduced dose in EGFR mutant non-small cell lung carcinoma. Issue 10 (November 2019) - Kwok, Wang Chun; Ho, James Chung Man; Tam, Terence Chi Chun; Lui, Macy Mei Sze; Ip, Mary Sau Man; Lam, David Chi Leung
Abstract : As a first-generation epidermal growth factor receptor-tyrosine kinase inhibitor, gefitinib was approved by the US Food and Drug Administration for treatment of advanced non-small cell carcinoma with sensitizing EGFR mutations. Gefitinib is known to have adverse effects, which may necessitate dose reduction or even change to alternative preparation of epidermal growth factor receptor-tyrosine kinase inhibitor. There has been concern on dose reduction resulting in reduced dose gefitinib, especially on its efficacy. This was a retrospective single-center cohort study conducted in Queen Mary Hospital in Hong Kong that included 159 Chinese patients with advanced adenocarcinoma of lung that carried sensitizing EGFR mutations and had received gefitinib as first-line treatment. Patients who had reduced dose at 250 mg alternate day were compared with those who were able to maintain on standard dose of gefitinib at 250 mg daily. The primary end-point was progression-free survival. Among the 159 patients, 17 (10.7 %) of them were on reduced dose gefitinib, 14 among the 17 patients (82.4%) because of hepatotoxicity, and 3 (17.6%) because of cutaneous side effects. Patients on reduced dose and standard dose of gefitinib have comparable median progression-free survival. Hazard ratio was 1.121 (95% confidence interval = 0. 655–1.917, P -value = 0.678) for the reduced dose group and 3.385 for the standard dose group (95% confidence interval = 2.181–5.255) respectively ( P -value < 0.001). Dose reduction in gefitinib to 250 mg alternate day in response to adverse effects was not associated with inferior outcome for patients on first-line gefitinib for advanced non-small cell carcinoma. Dose reduction is a feasible option for patients who have significant adverse effects with gefitinib.